The imperiled ocean : human stories from a changing sea - Trethewey, Laura (Pegasus Books, 2019)
On a life raft in the Mediterranean, a teenager from Ghana wonders whether he will reach Europe alive, and if he does, whether he will be allowed to stay. In the North Atlantic, a young chef disappears from a cruise ship, leaving a mystery for his friends and family to solve. A water-squatting community battles eviction from a harbor in a Pacific Northwest town, raising the question of who owns the water. Imperiled Ocean by ocean journalist Laura Trethewey is a deeply reported work of narrative journalism that follows people as they head out to sea. What they discover holds inspiring and dire implications for the life of the ocean <U+2015> and for all of us back on land. As Imperiled Ocean unfolds, battles are fought, fortunes made, lives lost, and the ocean approaches an uncertain future. Behind this human drama, the ocean is growing ever more unstable, threatening to upend life on land. As we explore with Tretheway, we meet biologist Erin Stoddard tracking sturgeon in the Pacific Northwest. Unable to stop the development and pollution destroying the fish<U+2019>s habitat, Stoddard races to learn about the fish before it disappears. This prehistoric fish has survived more than 300 million years on earth and could hold important truths about how humanity might make itself amenable to a changing ocean. As a fisher and scientist, Erin<U+2019>s ability to listen to the water becomes a parable for what faces the ocean today. By eavesdropping on an imperiled world, he shows a way we can move forward to save the oceans we all share<U+2015>through listening and discovery.